(1x+6)-(2x+7)-3x=9

Simple and best practice solution for (1x+6)-(2x+7)-3x=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1x+6)-(2x+7)-3x=9 equation:


Simplifying
(1x + 6) + -1(2x + 7) + -3x = 9

Reorder the terms:
(6 + 1x) + -1(2x + 7) + -3x = 9

Remove parenthesis around (6 + 1x)
6 + 1x + -1(2x + 7) + -3x = 9

Reorder the terms:
6 + 1x + -1(7 + 2x) + -3x = 9
6 + 1x + (7 * -1 + 2x * -1) + -3x = 9
6 + 1x + (-7 + -2x) + -3x = 9

Reorder the terms:
6 + -7 + 1x + -2x + -3x = 9

Combine like terms: 6 + -7 = -1
-1 + 1x + -2x + -3x = 9

Combine like terms: 1x + -2x = -1x
-1 + -1x + -3x = 9

Combine like terms: -1x + -3x = -4x
-1 + -4x = 9

Solving
-1 + -4x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -4x = 9 + 1

Combine like terms: -1 + 1 = 0
0 + -4x = 9 + 1
-4x = 9 + 1

Combine like terms: 9 + 1 = 10
-4x = 10

Divide each side by '-4'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| W^2+2w-392=0 | | a^2-2a-3= | | 2+.075x=x | | 10x=15-3(x-3) | | -7=-3x^2-2x | | x^2-5x+8=-2 | | 12+5x=7(-6+8x)+3 | | 110=-2(-7r+1) | | 7x+(3x-6)= | | X^2-8x-4y+12=0 | | 3+-5x=54 | | 25xsquared+30x+9=0 | | 0=x^2+12x+20 | | -6y=4x+2 | | 3(2y-2)-y=-5 | | -7n+5=-6n-15 | | -0.8x^2+12x+y=25.8 | | 52=-5x-3 | | 7a+5=19 | | x-240=(-6) | | 2v-2=4 | | 8-2q=2 | | 0.5x+7=58 | | 3x+5=7(x+3) | | 3x+5=7(x+5) | | 7=3u-2 | | 12x-9=4x+13 | | 2(n^2+n-17)=0 | | 4x+-5=2x+3 | | 5x(2-6)=4xy | | 84=6n+5(n+8) | | 5(x+4)+x=2x+3(x+12) |

Equations solver categories